Numerical study on combined thermal radiation and magnetic field effects on entropy generation in unsteady fluid flow past an inclined cylinder. Issue 1 (12th October 2020) - Mburu, Zachariah Mbugua; Mondal, Sabyasachi; Sibanda, Precious
Abstract: This study reports on combined thermal radiation, chemical reaction, and magnetic field effects on entropy generation in an unsteady nanofluid flow past an inclined cylinder using the Buongiorno model. We consider the impact of viscous dissipation, velocity slip conditions, thermal slip conditions, and the Brownian motion. The transport equations governing the flow are solved using an overlapping grid spectral collocation method. The results indicate that entropy generation is suppressed significantly by thermal radiation and chemical reaction parameters but enhanced with the magnetic field, viscous dissipation, the Brinkman number, and the Reynolds number. Also, fluid flow variables are affected by the thermophoresis parameter, the angle of cylinder inclination, and the Richardson number. We present the findings of the skin friction coefficient, the Nusselt number, and the Sherwood number. The model is applicable in fields such as the petroleum industry, building industries, and medicine. Graphical Abstract: